CHANGE MANAGEMENT STRATEGY AT DARUL FALAH SMP BANDAR LAMPUNG - Hamiyah, Hamiyah; Putri, Karomah Yuliana; Habib, Muhammad Raihan; Wijaya, Rahman; Hadiati, Eti; Elice, Deti (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Change management in education is a strategy designed to deal with various challenges arising from the development of the times, policy changes, and the needs of society. This study aims to explore the implementation of change management as an effort to improve the quality of education in formal institutions, by focusing on the planning, implementation, and evaluation stages of change. The research approach used is qualitative descriptive, with data collection techniques through in-depth interviews, participatory observations, and documentation studies. The focus of this research involves identifying key elements that affect the success of change management, such as transformational leadership, active participation of stakeholders, readiness of educators and learners, and strategies to manage resistance to change. The results show that the successful implementation of change is highly dependent on strategic planning, open and transparent communication, continuous training for educators, and cross-sector collaboration. Leaders who are able to inspire and empower the team are an important factor in driving change in a positive direction. In addition, resistance to change can be minimized by building collective awareness of the long-term benefits of each new policy implemented. Institutions that have an adaptive learning culture tend to be better prepared to face change and are able to create innovations that contribute to improving the quality of education. This research makes a significant academic contribution by presenting a conceptual and applicable framework for the implementation of change management in the context of education. Thus, these findings are expected to be a guide for educational institutions and stakeholders to design sustainable change strategies. This study emphasizes that with the right approach, change management not only improves the quality of learning, but also supports the achievement of national education goals in creating superior and competitive human resources.